The Effects of Chinese Medicine QRD, Antibiotics, and Probiotics on Therapy and Gut Microbiota in Septic Rats - Cao, Huiling; Zong, Chunhui; Dai, Wenkui; Gao, Qiaoying; Li, Donghua; Wu, Xianzhong; Li, Dongfang; Tang, Yi-Wei; Wu, Shangwei (Frontiers in Cellular and Infection Microbiology, 2021)
Sepsis is a common and often treacherous medical emergency with a high mortality and long-term complications in survivors. Though antibiotics therapy can reduce death rate significantly, it impairs gut microbiota (GM) which imbalance in sepsis and imperative role in health recovery are demonstrated. In this study, we compared the different effects of antibiotics (AT), probiotics (PT) and Chinese medicine QRD (QT) on survival rate as well as intestinal microbiota of septic rats via 16S rRNA gene amplicon sequencing. The 72 h survival rate of rats treated with antibiotics or QRD were significantly higher than that of probiotics. GM in septic rats (ST group) was different from that in sham operation controls (SC group). Rats receiving antibiotics therapy had dramatically decreased GM diversity when compared to PT and QT group. In addition, septic rats in AT group had accumulated Escherichia Shigella, Proteus, Morganella, Enterococcus and Lysinibacillus, as well as decreased Parabacteroides, Alistipes, Desulfovibrio, Bacteroides, Helicobacter, Mucispirillum, Oscillibacter, Lachnospiraceae and Ruminiclostridium 9, as compared to PT and QT group. GM of rates in PT and QT group had similar diversity and structure. Our findings indicated that QRD treated sepsis effectively without impairing gut microbiota which provides additional insights into the role of Chinese medicine in therapy and long-term recovery of sepsis.